2021
DOI: 10.3389/fpsyg.2021.547773
|View full text |Cite
|
Sign up to set email alerts
|

Reality Meets Belief: A Mixed Methods Study on Character Strengths and Well-Being of Hospital Physicians

Abstract: Positive psychology deals with factors that make life most worth living and focuses on enhancing individual potentials. Particularly, character strengths can positively contribute to well-being and work-related health, bearing a promising potential for professions, such as physicians, who are at risk for burnout or mental illnesses. This study aims to identify beneficial character strengths by examining the quantitative and qualitative data. In a cross-sectional multi-method study, 218 hospital physicians comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Transcendence refers to appreciation of beauty and excellence, humor, faith and hope. The greater a person's courage, humanity, justice, and transcendence, the stronger their humanistic care ability (Kachel et al, 2021 ). It is possible that nursing students with more positive mental characters could provide services that better meet patients' needs, through effective patient communication, the observation of patient behavior and empathy with patients' emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcendence refers to appreciation of beauty and excellence, humor, faith and hope. The greater a person's courage, humanity, justice, and transcendence, the stronger their humanistic care ability (Kachel et al, 2021 ). It is possible that nursing students with more positive mental characters could provide services that better meet patients' needs, through effective patient communication, the observation of patient behavior and empathy with patients' emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the positive orientation of thoughts, emotions and behaviors of individuals is influenced by positive mental characters, which is reflected in the fact that individuals can maintain a positive and optimistic attitude when they are confused or in adversity, and are good at improving their self-quality when they are in good times, which has a positive effect on the caring behaviors of nursing students during their clinical practice (Park and Peterson, 2006 ; Celano et al, 2013 ; Kachel et al, 2021 ). Positive mental character was first mentioned by Meng et al ( 2016 ) based on the researches from Peterson and Seligman ( 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…46 Character Strengths, Professionalism, and Health Care Research on character strengths in health care has shown that both physicians and trainees identify certain character strengths as important to well-being in medicine: honesty, kindness, fairness, judgment, and love. 47 Furthermore, the character strengths of zest and hope have been linked empirically to health care professionals' work-related well-being and engagement. 20,47 This literature, however, reveals a concerning gap in character strengths deemed relevant to health care work relative to those associated with overall well-being.…”
Section: Defining Character As Strengthsmentioning
confidence: 99%
“…A study demonstrated the relationships between volunteer work and six aspects of personal well-being: happiness, life satisfaction, self-esteem, sense of control over life, physical health, and depression. The results showed that volunteer work improves all six aspects of well-being [ 62 ] and if the relevant departments can further measure the individual personality of different volunteers when arranging volunteer work, so that they can each share their strengths, it will not only improve the work results to a certain extent, but also further enhance the happiness level of each person in volunteer service [ 63 , 64 ]. Therefore, a successful volunteer service brings a certain value to others and society and immeasurable value to one’s life in the process [ 65 ].…”
Section: Volunteerism In the Practice Of Humanistic Education For Med...mentioning
confidence: 99%